2018
DOI: 10.1136/bmjsrh-2017-101866
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of TRAP laws on abortion and women’s health in the USA: a systematic review

Abstract: TRAP laws may have an impact on the experience of obtaining an abortion in the USA. However, our review revealed a paucity of empirical research on their population and individual-level impact, as well as some disagreement about the effect of different TRAP laws on subsequent abortion outcomes. Future research should prioritise the specific TRAP laws that may have a uniquely strong effect on state-level abortion rates and other outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…1 and Appendix 1). We included items about abortion laws (12), about common abortion myths (5), personal views on abortion (1), self-reported pregnancy and abortion history (3), and health literacy (6) [21].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 and Appendix 1). We included items about abortion laws (12), about common abortion myths (5), personal views on abortion (1), self-reported pregnancy and abortion history (3), and health literacy (6) [21].…”
Section: Methodsmentioning
confidence: 99%
“…While no outright abortion ban is currently in effect in any state, abortion access is widely variable based on legislation in each state [5,6]. Fifty-eight percent of reproductive-aged women live in states with policy hostile toward abortion [6].…”
Section: Introductionmentioning
confidence: 99%
“…A major impact of paternalism for r/abortion users resulted from policy variation between states, causing inequity and travel barriers. State Targeted Regulations of Abortion Providers (TRAP) impose clinical restrictions without directly criminalizing abortion [28]. Our analysis found that these factors were major barriers to r/abortion users, as they often discussed ways to mitigate restrictions through interstate travel.…”
Section: Discussionmentioning
confidence: 89%
“…In contrast, TRAP opponents argue that the structural barriers imposed by these laws harm women by making it more difficult to access abortion, which could lead to changes in abortion rates, increased gestational age at presentation (which subsequently leads to more expensive and complicated procedures), and possibly increases in self‐induced abortion . A recent systematic review of quantitative evidence on the health effects of supply‐side policies found a general lack of evidence on this topic, although the available studies did suggest an inverse association between enforcement of certain TRAP laws and abortion rates.…”
Section: Introductionmentioning
confidence: 99%